Preparation method of ceramic-based high-speed train brake pad and corresponding matched friction piece thereof
The ceramic-based high-speed train brake pads are prepared by discharge plasma sintering technology and matched with suitable friction parts materials, which solves the problem of unstable friction coefficient and wear rate of ceramic-based brake pads at high temperatures, and achieves high performance and low cost preparation of ceramic-based brake pads.
Patent Information
- Application Number
- CN202510037122.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-09
- Publication Date
- 2025-03-28
AI Technical Summary
The existing ceramic-based high-speed train brake pads have unstable friction coefficient and wear rate at high temperatures, and the preparation period is long and costly, making it difficult to meet the needs of high-speed train braking systems.
Discharge plasma sintering technology is used to prepare ceramic-based high-speed train brake pads. By adjusting chemical composition and sintering parameters, brake pad materials with appropriate hardness are prepared, and suitable friction material (such as Al2O3 or Si3N4) are selected to match.
The prepared ceramic-based high-speed train brake pad has excellent mechanical and frictional properties, and has good matching properties with the friction parts. It can maintain stable frictional properties and low wear rate at high temperatures, reducing the production cost and cycle.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The invention relates to a method for preparing a ceramic-based high-speed train brake pad and a corresponding matching friction piece. Background Art
[0002] With the development of train technology and the increase in speed, the surface temperature of the friction plate rises sharply during braking, and the transient temperature can reach 1000°C. At present, the key point of domestic and foreign scholars' research on friction plate materials is the stability of the friction coefficient and wear rate, that is, the room temperature and high temperature remain basically unchanged. Among them, the most important key point is the stability of the friction coefficient and wear rate at high temperature. This is because the oxidation rate increases sharply with the increase in temperature, resulting in a sharp change in the friction coefficient and wear rate. Although C / C-based friction materials can effectively solve the stability of high-temperature friction coefficient and wear rate, the preparation cycle is long and the preparation cost is high, which is not suitable for widespread application. Therefore, the research and development of new ceramic-based friction materials with shorter preparation cycles and lower preparation costs to replace C / C-based friction materials is of great significance to the development of braking systems.
[0003] Ceramic-based high-speed train brake pads are one of the important development directions of train brake pads. Due to its excellent high-temperature stability, good wear resistance and excellent braking performance, it has been widely used in the braking system of high-speed trains. However, the research and development of ceramic-based high-speed train brake pads is difficult, and many factors need to be considered, such as the mechanical properties and friction properties of the material. In the research and development process of ceramic-based high-speed train brake pads, in addition to considering the mechanical properties and friction properties of the brake pad materials, it is also necessary to consider the matching of the corresponding friction parts; due to the high hardness of ceramic-based high-speed train brake pads, the matching between the friction parts also needs to be fully considered to ensure the service life and performance of the brake pads.
[0004] The present invention relates to the material preparation of ceramic-based high-speed train brake pads, and the prepared brake pads have excellent mechanical and friction properties. In addition, the ceramic-based high-speed train brake pad material is matched with the friction parts. This ensures that the matching between the ceramic-based high-speed train brake pads and the friction parts can meet the needs of practical applications. Therefore, the innovation of the present invention is not only the preparation of ceramic-based brake pad materials with excellent mechanical and friction properties, but also the matching of brake pad materials with friction parts. The present invention has a high practical application value. Summary of the invention
[0005] The main purpose of the present invention is to prepare a ceramic-based high-speed train brake pad by spark plasma sintering, and select corresponding friction parts according to the hardness of the brake pad material.
[0006] The ceramic-based high-speed train brake pad preparation method and the corresponding matching friction parts in the present invention are characterized in that the chemical components are as follows by mass percentage: titanium powder 35.67-73.44wt.%, silicon powder 6.97-23.21wt.%, graphite powder 0-25wt.%, carbon fiber 0-13.33wt.%, aluminum powder 0-2.68wt.%, 304L stainless steel powder 0-50wt.%; all raw material powders are single powders with a purity of 99%; except for carbon fiber with a length of 3mm and a diameter of 7nm, the particles of other raw material powders are all <45μm.
[0007] The above ceramic-based high-speed train brake pad preparation method and its corresponding matching friction parts: (1) Mill titanium powder, silicon powder, graphite powder, carbon fiber, aluminum powder, and 304L stainless steel powder in a ball mill with a ball-to-material mass ratio of 2:1-10:1, a set speed of 200-400 r / min, and a ball milling time of 3-10 h.
[0008] (2) The ball-milled powder is loaded into a cemented carbide mold, pre-pressed and molded under a pressure of 50-300 MPa, and then spark plasma sintered. The sintering pressure is 20-50 MPa, the sintering temperature is 1100-1800 °C, and the temperature is raised from room temperature to the target temperature at a rate of 60-90 °C / min. After reaching the target sintering temperature, the temperature is kept for 1-30 min to obtain a sintered body of a ceramic-based high-speed train brake pad. The surface of the prepared sintered body is ground and polished to obtain a ceramic-based high-speed train brake pad material.
[0009] (3) When preparing ceramic-based high-speed train brake pad materials with a hardness higher than 11 GPa, the friction material selected is Al2O3 or Si3N4, while when preparing ceramic-based high-speed train brake pad materials with a hardness lower than 11 GPa, the friction material selected is 45# steel.
[0010] The ceramic-based high-speed train brake pad prepared by the present invention not only has excellent mechanical and friction properties, but also matches the brake pad material with the corresponding friction parts, and has high practical application value. DETAILED DESCRIPTION Example 1
[0012] By mass percentage, 65.69wt.% of titanium powder, 14.31wt.% of silicon powder, 20wt.% of graphite powder, 0wt.% of carbon fiber, 0wt.% of aluminum powder, and 0wt.% of 304L stainless steel powder were put into a WC cemented carbide tank. The purity of all raw powders was 99%, the mesh size was 200 mesh, the ball-to-material ratio was 2:1, and the ball milling medium was WC cemented carbide balls. After repeated gas washing (argon gas) in the transition cabin of the glove box, they were put into the operating chamber and covered with a sealing cover to ensure that the tank was taken out under the argon environment and put into the ball mill. The ball milling speed was 200 r / min, and the forward and reverse rotations were alternately operated. The forward rotation was 1 h and the machine was stopped for 30 min, and then the reverse rotation was 1 h. This cycle was repeated and all the powder was taken out after 3 h of ball milling.
[0013] The ball-milled raw material powder was filled into a graphite mold pre-installed with graphite pad paper, and the obtained preformed sample was placed in a discharge plasma system for sintering experiment after pre-pressing with a hydraulic press at a pressure of 50 MPa. The experiment adopted a sintering temperature of 1500 ℃ at 40 MPa, a heating rate of 80 ℃ / min, and kept at 1500 ℃ for 10 min, then unloaded the pressure and slowly cooled to room temperature to obtain the material of ceramic-based high-speed train brake pads.
[0014] The obtained ceramic-based high-speed train brake pad material was ground and polished, and then the structure and performance were tested using instruments used in conventional testing methods. The obtained technical parameters are as follows:
[0015] The mechanical and friction properties of the prepared ceramic-based high-speed train brake pads have great advantages over traditional metals, and the matching between the selected Al2O3 or Si3N4 friction parts and the brake pads can meet the needs of practical applications, and the wear rates at room temperature and 500℃ are low. Example 2
[0016] By mass percentage, 71.48wt.% of titanium powder, 13.94wt.% of silicon powder, 0wt.% of graphite powder, 11.91wt.% of carbon fiber, 2.68wt.% of aluminum powder, and 0wt.% of 304L stainless steel powder were put into a WC cemented carbide tank. The purity of all raw powders was 99%, the ball-to-material ratio was 2:1, and the ball milling medium was WC cemented carbide balls. After repeated gas washing (argon gas) in the transition cabin of the glove box, they were put into the operating chamber and covered with a sealing cover to ensure that the tank was taken out and placed in the ball mill under the argon environment. The ball milling speed was 300 r / min, and the forward and reverse rotation were alternating. The forward rotation was 1 h and the machine was stopped for 30 min, and then the reverse rotation was 1 h. This cycle was repeated. After 5 h of ball milling, all the powder was taken out.
[0017] The ball-milled raw material powder was filled into a graphite mold pre-installed with graphite pad paper, and pre-pressed with a hydraulic press at a pressure of 300 MPa, and the obtained prefabricated sample was placed in a discharge plasma system for sintering experiments. The experiment used a sintering temperature of 1800 ℃ at 50 MPa, a heating rate of 90 ℃ / min, and kept at 1800 ℃ for 30 min, then unloaded the pressure and slowly cooled to room temperature to obtain a ceramic-based high-speed train brake pad material.
[0018] The obtained ceramic-based high-speed train brake pad material was ground and polished, and then the structure and performance were tested using instruments used in conventional testing methods. The obtained technical parameters are as follows:
[0019] The mechanical and friction properties of the prepared ceramic-based high-speed train brake pads have great advantages over traditional metals, and the matching between the selected Al2O3 or Si3N4 friction parts and the brake pads can meet the needs of practical applications, and the wear rates at room temperature and 500℃ are low. Example 3
[0020] By mass percentage, 42.88wt.% of titanium powder, 8.36wt.% of silicon powder, 0wt.% of graphite powder, 7.15wt.% of carbon fiber, 1.61wt.% of aluminum powder, and 40wt.% of 304L stainless steel powder were put into a WC cemented carbide tank. The purity of all raw powders was 99%, the ball-to-material ratio was 4:1, and the ball milling medium was WC cemented carbide balls. After repeated gas washing (argon gas) in the transition cabin of the glove box, they were put into the operating chamber and covered with a sealing cover to ensure that the tank was taken out and placed in the ball mill under the argon environment. The ball milling speed was 400 r / min, and the forward and reverse rotation were alternating. The forward rotation was 1 h and the machine was stopped for 30 min, and then the reverse rotation was 1 h. This cycle was repeated. After 8 h of ball milling, all the powder was taken out.
[0021] The ball-milled raw material powder was filled into a graphite mold pre-installed with graphite pad paper, and pre-pressed with a hydraulic press at a pressure of 100 MPa. The obtained prefabricated sample was placed in a discharge plasma system for sintering experiments. The experiment used a sintering temperature of 1200 ℃ at 50 MPa, a heating rate of 70 ℃ / min, and was kept at 1200 ℃ for 1 min. Then the pressure was unloaded and the temperature was slowly cooled to room temperature to obtain a ceramic-based high-speed train brake pad material.
[0022] The obtained ceramic-based high-speed train brake pad material was ground and polished, and then the structure and performance were tested using instruments used in conventional testing methods. The obtained technical parameters are as follows:
[0023] The mechanical and friction properties of the prepared ceramic-based high-speed train brake pads have great advantages over traditional metals, and the matching between the selected Al2O3 or Si3N4 friction parts and the brake pads can meet the needs of practical applications, and the wear rates at room temperature and 500℃ are low. Example 4
[0024] By mass percentage, 64.32wt.% of titanium powder, 12.55wt.% of silicon powder, 0wt.% of graphite powder, 10.72wt.% of carbon fiber, 2.41wt.% of aluminum powder, and 10wt.% of 304L stainless steel powder were put into a WC cemented carbide tank. The purity of all raw material powders was 99%, the ball-to-material ratio was 8:1, and the ball milling medium was WC cemented carbide balls. After repeated gas washing (argon gas) in the transition cabin of the glove box, they were put into the operating chamber and covered with a sealing cover to ensure that the tank was taken out and put into the ball mill under the argon environment. The ball milling speed was 200 r / min, and the forward and reverse rotation were alternating. The forward rotation was 1 h and the machine was stopped for 30 min, and then the reverse rotation was 1 h. This cycle was repeated. After 6 h of ball milling, all the powder was taken out.
[0025] The ball-milled raw material powder was filled into a graphite mold pre-installed with graphite pad paper, and pre-pressed with a hydraulic press at a pressure of 100 MPa, and then the prefabricated sample was placed in a discharge plasma system for sintering experiments. The experiment used a sintering temperature of 1200 ℃ at 20 MPa, a heating rate of 70 ℃ / min, and a heat preservation of 1200 ℃ for 1 min, then unloaded the pressure and slowly cooled to room temperature to obtain a ceramic-based high-speed train brake pad material.
[0026] The obtained ceramic-based high-speed train brake pad material was ground and polished, and then the structure and performance were tested using instruments used in conventional testing methods. The obtained technical parameters are as follows:
[0027] The mechanical and friction properties of the prepared ceramic-based high-speed train brake pads have great advantages over traditional metals, and the matching between the selected Al2O3 or Si3N4 friction parts and the brake pads can meet the needs of practical applications, and the wear rates at room temperature and 500℃ are low. Example 5
[0028] By mass percentage, 61.10wt.% of titanium powder, 11.92wt.% of silicon powder, 5wt.% of graphite powder, 10.18wt.% of carbon fiber, 2.29wt.% of aluminum powder, and 9.5wt.% of 304L stainless steel powder were put into a WC cemented carbide tank. The purity of all raw powders was 99%, the ball-to-material ratio was 4:1, and the ball milling medium was WC cemented carbide balls. After repeated gas washing (argon gas) in the transition cabin of the glove box, they were put into the operating chamber and covered with a sealing cover to ensure that the tank was in an argon environment. Then they were taken out and put into the ball mill. The ball milling speed was 350 r / min, and the forward and reverse rotations were alternately operated. The forward rotation was 1 h and the machine was stopped for 30 min, and then the reverse rotation was 1 h. This cycle was repeated. After 8 h of ball milling, all the powder was taken out.
[0029] The ball-milled raw material powder was filled into a graphite mold pre-installed with graphite pad paper, and the preformed sample was pre-pressed at a pressure of 50 MPa using an oil press, and then placed in a discharge plasma system for sintering experiments. The experiment used a sintering temperature of 1200 ℃ at 40 MPa, a heating rate of 80 ℃ / min, and was kept at 1200 ℃ for 1 min, then the pressure was unloaded and the temperature was slowly cooled to room temperature to obtain a ceramic-based high-speed train brake pad material.
[0030] The obtained ceramic-based high-speed train brake pad material was ground and polished, and then the structure and performance were tested using instruments used in conventional testing methods. The obtained technical parameters are as follows:
[0031] The mechanical and friction properties of the prepared ceramic-based high-speed train brake pads have great advantages over traditional metals, and the matching between the selected 45# steel friction parts and the brake pads can meet the needs of practical applications, and the wear rates at room temperature and 500 ℃ are both low. Example 6
[0032] By mass percentage, 59.82wt.% of titanium powder, 11.67wt.% of silicon powder, 7wt.% of graphite powder, 9.97wt.% of carbon fiber, 2.24wt.% of aluminum powder, and 9.3wt.% of 304L stainless steel powder were placed in a WC cemented carbide tank. The purity of all raw powders was 99%, the ball-to-material ratio was 6:1, and the ball milling medium was WC cemented carbide balls. After repeated gas washing (argon gas) in the transition cabin of the glove box, they were placed in the operating chamber and covered with a sealing cover to ensure that the tank was taken out and placed in a ball mill under the argon environment. The ball milling speed was 200 r / min, and the forward and reverse rotations were alternately operated. The forward rotation was 1 h and the machine was stopped for 30 min, and then the reverse rotation was 1 h. This cycle was repeated and all the powder was taken out after 3 h of ball milling.
[0033] The ball-milled raw material powder was filled into a graphite mold pre-installed with graphite pad paper, and pre-pressed with an oil press at a pressure of 100 MPa, and then the prefabricated sample was placed in a discharge plasma system for sintering experiments. The experiment used a sintering temperature of 1200 ℃ at 20 MPa, a heating rate of 90 ℃ / min, and a heat preservation of 1200 ℃ for 1 min, then unloaded the pressure and slowly cooled to room temperature to obtain a ceramic-based high-speed train brake pad material.
[0034] The obtained ceramic-based high-speed train brake pad material was ground and polished, and then the structure and performance were tested using instruments used in conventional testing methods. The obtained technical parameters are as follows:
[0035] The mechanical and friction properties of the prepared ceramic-based high-speed train brake pads have great advantages over traditional metals, and the matching between the selected 45# steel friction parts and the brake pads can meet the needs of practical applications, and the wear rates at room temperature and 500 ℃ are both low. Example 7
[0036] By mass percentage, 59.12wt.% of titanium powder, 12.88wt.% of silicon powder, 10wt.% of graphite powder, 0wt.% of carbon fiber, 0wt.% of aluminum powder, and 10wt.% of 304L stainless steel powder were put into a WC cemented carbide tank. The purity of all raw powders was 99%, the ball-to-material ratio was 10:1, and the ball milling medium was WC cemented carbide balls. After repeated gas washing (argon gas) in the transition cabin of the glove box, they were put into the operating chamber and covered with a sealing cover to ensure that the tank was taken out under the argon environment and put into the ball mill. The ball milling speed was 400 r / min, and the forward and reverse rotation were alternating. The forward rotation was 1 h and the machine was stopped for 30 min, and then the reverse rotation was 1 h. This cycle was repeated. After 10 h of ball milling, all the powder was taken out.
[0037] The ball-milled raw material powder was filled into a graphite mold pre-installed with graphite pad paper, and the preformed sample was pre-pressed at a pressure of 200 MPa using an oil press, and then placed in a discharge plasma system for sintering experiments. The experiment used a sintering temperature of 1500 ℃ at 50 MPa, a heating rate of 60 ℃ / min, and was kept at 1500 ℃ for 1 min, then the pressure was unloaded and the temperature was slowly cooled to room temperature to obtain a ceramic-based high-speed train brake pad material.
[0038] The obtained ceramic-based high-speed train brake pad material was ground and polished, and then the structure and performance were tested using instruments used in conventional testing methods. The obtained technical parameters are as follows:
[0039] The mechanical and friction properties of the prepared ceramic-based high-speed train brake pads have great advantages over traditional metals, and the matching between the selected 45# steel friction parts and the brake pads can meet the needs of practical applications, and the wear rates at room temperature and 500 ℃ are both low.
[0040] In summary, the ceramic-based high-speed train brake pad prepared by the present invention not only has excellent mechanical and friction properties, but also matches the brake pad material with the corresponding friction parts, and has high practical application value.
[0041] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit them. Although the present invention has been described in detail with reference to the above embodiments, a person skilled in the art should understand that the technical solutions described in the above embodiments can still be modified, or some or all of the technical features can be replaced by equivalents; and these modifications or replacements do not make the essence of the corresponding technical solutions deviate from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. A method for preparing a ceramic-based high-speed train brake pad, characterized in that: include: Step (1) grinding several of titanium powder, silicon powder, graphite powder, carbon fiber, aluminum powder, and 304L stainless steel powder in a ball mill, with a ball-to-material mass ratio of 2:1-10:1, using three different sizes of hard alloy balls (diameters of 1 mm, 4 mm, and 6 mm, respectively) of large, medium, and small, with a corresponding mass ratio of large, medium, and small balls of 1:3:6, setting the rotation speed to 200-400 r / min, running alternately, stopping for 20 minutes every hour, and accumulating a ball milling time of 3-10 hours; then manually crushing the alloy powder bonded to the bottom of the ball mill in a glove box, and separating the raw material powder from the grinding balls in the glove box after ball milling to obtain a ceramic-based high-speed train brake pad powder; Step (2) the ball-milled raw material powder is filled into a cemented carbide mold, pre-pressed under a pressure of 50-300 MPa, and then loaded into a graphite mold for spark plasma sintering, the sintering pressure is 20-50 MPa, the sintering temperature is 1100-1800°C, the temperature is raised from room temperature to the target temperature at a rate of 60-90°C / min, and the temperature is kept at the target temperature for 1-30 min to obtain a sintered body of a ceramic-based high-speed train brake pad; Step (3) grinding and polishing the surface of the sintered body prepared in step (2) to remove the graphite remaining on the surface of the sample sintered body and the burrs generated on the edge during the sintering process, thereby preparing a ceramic-based high-speed train brake pad material; Step (4) matches the ceramic-based high-speed train brake pad prepared in step (3) with a friction part; Al2O3 or Si3N4 is selected as the friction part material for preparing a brake pad material with a hardness higher than 11 GPa, and 45# steel is selected as the friction part material for preparing a brake pad material with a hardness lower than 11 GPa.
2. A corresponding matching friction piece of the method for preparing a ceramic-based high-speed train brake pad according to claim 1, characterized in that: The chemical composition mass percentage is: titanium powder 35.67-73.44wt.%, silicon powder 6.97-23.21wt.%, graphite powder 0-25wt.%, carbon fiber 0-13.33wt.%, aluminum powder 0-2.68wt.%, 304L stainless steel powder 0-50wt.%.
3. The corresponding matching friction piece of the method for preparing a ceramic-based high-speed train brake pad according to claim 2 is characterized in that: All raw material powders are single-element powders with a purity of 99%; except for carbon fibers with a length of 3mm and a diameter of 7nm, the particles of other raw material powders are all <45μm.